Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006966.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Open versus closed surgical exposure of canine teeth that are displaced in the roof of the mouth

Abstract: This review has revealed that currently, there is no evidence to support one surgical technique over the other in terms of dental health, aesthetics, economics and patient factors. Until high quality clinical trials with participants randomly allocated into the two treatment groups are conducted, methods of exposing canines will be left to the personal choice of the surgeon and orthodontist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…10,11 A recent Cochrane systematic review found no robust evidence to support one surgical technique over the other. 12 The principal purpose of this trial was to explore any differences in the periodontal health between canines exposed using an Open versus a Closed surgical technique. Differences in periodontal health between canines that have had an operation (those that were palatally displaced and had been surgically exposed) versus the contralateral canines that have not undergone an operation (and can act as a control) were also examined.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 A recent Cochrane systematic review found no robust evidence to support one surgical technique over the other. 12 The principal purpose of this trial was to explore any differences in the periodontal health between canines exposed using an Open versus a Closed surgical technique. Differences in periodontal health between canines that have had an operation (those that were palatally displaced and had been surgically exposed) versus the contralateral canines that have not undergone an operation (and can act as a control) were also examined.…”
Section: Introductionmentioning
confidence: 99%
“…6 Proponents of each technique claim certain advantages; however a recent Cochrane collaboration systematic review was unable to find any evidence to support the use of one technique over the other. 7 The purpose of this study was to determine if there are any differences in the outcomes between the Open and Closed surgical techniques for exposing a PDC. In this report the investigators tested the null hypothesis that there would be no difference in the surgical outcomes between the two techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found no evidence of the superiority in terms of clinical attachment levels following treatment of one technique over the other. 2 A recent randomized controlled trial has confirmed this. 3 One outcome that has received limited investigation is the esthetic appearance of the PDC, following surgical exposure and alignment D A 4 obtained the esthetic judgments of orthodontists and patients concerning displaced canines that had been exposed using a closed surgical technique and orthodontically aligned.…”
Section: Introductionmentioning
confidence: 88%